2009
DOI: 10.1021/nl902200b
|View full text |Cite
|
Sign up to set email alerts
|

Solution Phase Production of Graphene with Controlled Thickness via Density Differentiation

Abstract: Graphene flakes with controlled thicknesses are isolated in solution using density gradient ultracentrifugation. These stable graphene dispersions are produced using the bile salt sodium cholate, which promotes graphite exfoliation and results in graphene-surfactant complexes having buoyant densities that vary with graphene thickness. The sorted graphene flakes are characterized using atomic force microscopy and Raman spectroscopy. Graphene dispersions produced using density differentiation offer superior perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
652
3
5

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 720 publications
(688 citation statements)
references
References 38 publications
28
652
3
5
Order By: Relevance
“…Simulation studies confirmed that planar SC molecules partially cover 60% of the graphene surface and are adsorbed parallel to the graphene surface to maximize the hydrophobic interactions [104,105]. However, the computed adsorption still falls short of the value reported by Green et al [106] estimating that 94% of the graphene surface is occupied and SDBS), the resulting dispersion did not consist entirely of single layer graphene, but a co-existing distribution with multilayer graphene (MLG). A study on graphene dispersion using SC was also reported by Tkalya et al [28].…”
Section: Accepted M Manuscriptmentioning
confidence: 83%
“…Simulation studies confirmed that planar SC molecules partially cover 60% of the graphene surface and are adsorbed parallel to the graphene surface to maximize the hydrophobic interactions [104,105]. However, the computed adsorption still falls short of the value reported by Green et al [106] estimating that 94% of the graphene surface is occupied and SDBS), the resulting dispersion did not consist entirely of single layer graphene, but a co-existing distribution with multilayer graphene (MLG). A study on graphene dispersion using SC was also reported by Tkalya et al [28].…”
Section: Accepted M Manuscriptmentioning
confidence: 83%
“…Based on the resulting FWHM of 2D band for our graphene (86 cm -1 ), and reported FWHM of 2D band for monolayer graphene (35 cm -1 ) (Green and Hersam 2009), the produced value of hNi for G GA seems to imply that majority of G GA sheets are bilayer when only FWHM of 2D band was concerned. However, this resulting value is not accurate enough as the proposed metric is only suitable for thickness measurement of single graphene sheet (Green and Hersam 2009) and not for vacuum-filtered graphene film. Moreover, our produced graphene is not as pristine as the metric required due to its functionalisation with gum Arabic.…”
Section: Characterisations Of Graphenementioning
confidence: 92%
“…The mean layer number hNi of G GA meanwhile was evaluated from the Raman data through intensity ratio measurement of full-width half maximum (FWHM) for 2D band (Green and Hersam 2009). Based on the resulting FWHM of 2D band for our graphene (86 cm -1 ), and reported FWHM of 2D band for monolayer graphene (35 cm -1 ) (Green and Hersam 2009), the produced value of hNi for G GA seems to imply that majority of G GA sheets are bilayer when only FWHM of 2D band was concerned.…”
Section: Characterisations Of Graphenementioning
confidence: 99%
“…Rational control over nanosheet thickness and size is likely to be required for nanoelectronics and in particular optoelectronics. Also by analogy with graphene, new layer-controlled chemistries 63 and post-synthesis sorting of flakes by layer thickness 64 and lateral size 65 may offer solutions.…”
mentioning
confidence: 99%